Humanistic Burden of Huntington Disease: Evidence From the Huntington Disease Burden of Illness Study. Issue 6 (December 2022) - Rodriguez Santana, Idaira; Frank, Samuel; Doherty, Maria; Willock, Rosa; Hamilton, Jamie; Hubberstey, Hayley; Stanley, Cath; Vetter, Louise; Winkelmann, Michaela; Dolmetsch, Ricardo E.; Li, Nanxin; Ratsch, Sarah; et al.
Abstract : Background and Objectives: Huntington disease (HD) is a rare, inherited, and highly complex neurodegenerative disorder with no currently approved disease-modifying treatments. We investigated the effect of HD on health-related quality of life and other patient-reported outcomes in the Huntington's Disease Burden of Illness (HDBOI) study. Methods: The HDBOI study is a retrospective, cross-sectional study conducted between September 2020 and May 2021 in France, Germany, Italy, Spain, the United Kingdom, and the United States. People with symptomatic onset HD (PwHD) were recruited by their HD-treating physicians and categorized as early (ES), mid (MS), or advanced stage (AS) HD. Physicians provided sociodemographic and clinical information from the participant's medical records in electronic case report forms (eCRF); participants or their proxies completed online Patient Public Involvement Engagement questionnaires (PPIE-P). Patient-reported outcomes included the 5-level EQ-5D version (EQ-5D-5L), Short-Form-(SF)-36 v2 (and SF-6-Dimension [SF-6D] utility), Huntington Quality of Life Instrument (H-QoL-I), and the Work Productivity and Activity Impairment Specific Health Problem. All outcomes were summarized using descriptive statistics, and differences between disease stages were assessed by Kruskal-Wallis tests. Results: A total of 2, 094 PwHD were enrolled with completed eCRFs (100%) and PPIE-P forms (n = 482, 23%). Participants' mean age was 47.3 years; they were generally evenly distributed across countries, with the majority being ES (40%) followed by MS (33%) and LS (26%). The mean EQ-5D-5L (n = 336) utility score was 0.59 (SD, 0.27), with the highest mean utility scores [SD] in ES (0.72 [0.22]) followed by MS (0.62 [0.18]) and AS (0.37 [0.30]), p < 0.001. The mean SF-6D score (n = 482) was 0.57 (SD, 0.10), with mean values decreasing with advanced disease (ES, 0.61; MS, 0.56; AS, 0.50, p < 0.001). H-QoL-I mean scores (n = 482) also worsened with more advanced disease, from 0.58 for ES to 0.49 for MS and 0.37 for AS, p < 0.001. Impairment in daily activities and in work productivity also increased with more advanced disease. Overall proxy respondents reported on average worse outcomes than PwHD (self-reported) across all outcomes and disease stages suggesting a possible unawareness of deficits by PwHD. Discussion: The HDBOI study provides new insights into the characteristics and humanistic burden of PwHD and offers a meaningful contribution to this underserved research area.